An Investigation into Changes in The Situation of Science Teachers Who Attend Out-of-School Learning Activities - Hasan Özyıldırım; Ebru Durel; Eylem Bayır (Journal of Science Learning, 2023)
This study aims to investigate the situation of science teachers regarding out-of-school learning activities and to investigate how their participation in out-of-school learning activities as an observer within the scope of science courses creates a change in the situation of teachers. A case study was used in this study. Twenty-one science teachers in the study group participated as observers in the activities carried out with the seventh-grade students for seven different out-of-school learning areas. Pre- and post-interview forms were given to the study group. The findings demonstrate that a significant number of science teachers did not receive training for such practices before participating in the activities. They were aware of the benefits and importance of out-of-school activities but did not feel sufficient in learning practices. Another result of this study is that there are positive developments in the situation of teachers by showing a significant reduction in anxiety about aspects such as determining out-of-school learning environments according to the subject and performing out-of-school activities. In addition, this study reveals that teachers ’ observation experience makes them aware of different aspects of out-of-school learning.